Traditional Birth Attendance (TBAs) and health of women of child-bearing age in rural Areas of Ogoja Local Government Area, Nigeria - Bassey Immaculata Etim; Dr Bassey Emmanuel Etim; Scholarstica Asima Okpo (Journal of Medical Care Research and Review, 2024)
Aim: This study assessed the relationship between Traditional Birth Attendance (TBAs) and health of women of child-bearing age in rural Areas of Ogoja Local Government Area, Nigeria. Method: The survey research design was adopted in this study. the purposive and accidental random sampling techniques were adopted in selecting the 300 respondents sampled for the study from the population. A validated 12 items four-point modified Likert scale questionnaire was the instrument used for data collection. The face and content validity of the instrument was established by experts in Test and Measurement. The reliability estimates of 0.86 of the instruments were established using the test-retest method. Pearson’s Product Moment Correlation statistical tool was used to test the hypotheses formulated for the study. The hypothesis was tested at a 0.05 level of significance. Results: The results obtained from the data analysis revealed that there is a significant relationship between Traditional Birth Attendance (TBA) and health of women of child-bearing age in rural Areas of Ogoja Local Government Area, Nigeria. Conclusion: The finding concludes that there is a significant relationship between Traditional Birth Attendance (TBA) and health of women of child-bearing age in rural Areas of Ogoja Local Government Area, Nigeria. Recommendation: Based on the finding of the study it was recommended that It is important to train TBAs and provide them with the necessary resources to deliver appropriate services during pregnancy and labour in a holistic way, with much emphasis on the areas they find challenging such as cutting of the umbilical cord.